The delta subunit of Escherichia coli DNA polymerase III holoenzyme is the dnaX gene product. - Hübscher, U (1979)
The delta subunit of DNA polymerase III holoenzyme has been purified extensively with an assay for phi X174 DNA synthesis using core (pol III) and beta and gamma subunits. Either the purified delta subunit or the purified DNA polymerase III holoenzyme can complement a defective enzyme fraction from the conditional replication mutant SG133 described by Sevastopoulos et al. [Sevastopoulas, C.G., Wehr, C.T. & Glaser, D. A. (1977) Proc. Natl. Acad. Sci. USA 74, 3485-3489]. It has been established by Henson et al. [Henson, J.M., Chu, H., Irwin, C.A. & Walker, J.R. (1979) Genetics 92, 1,41-1059] that SG133 has two temperature-sensitive mutations, called dnaX and dnaY. The crude enzyme source from dnaX can be complemented by the delta subunit and by DNA polymerase III holoenzyme. By contrast, the core DNA polymerase III and the beta and gamma subunits are unable to complement this defective enzyme fraction. Thus, the delta subunit of DNA polymerase III holoenzyme appears to be the dnaX gene product of Escherichia coli.